2015
DOI: 10.1248/bpb.b14-00892
|View full text |Cite
|
Sign up to set email alerts
|

Paeoniflorin Protects against Nonalcoholic Fatty Liver Disease Induced by a High-Fat Diet in Mice

Abstract: Nonalcoholic fatty liver disease (NAFLD) is the most common chronic liver disease worldwide. Paeoniflorin, a natural product and active ingredient of Paeonia lactiflora, has been demonstrated to have many pharmacological effects including antiinflammatory and antihyperglycemic activity. We investigated the effects of paeoniflorin on NAFLD in mice and its underlying mechanisms. We examined this hypothesis using a well-established animal model of NAFLD. The effects of paeoniflorin on inflammation and glucolipid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
45
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 27 publications
4
45
0
1
Order By: Relevance
“…CYP7 α is the key rate-limiting enzyme for cholesterol transformation into bile acid in the liver, therefore promoting the excretion of cholesterol [19]. SREBP-2 is an important transcription factor, which could regulate fatty acid and cholesterol synthesis and impact the transcription of several genes involved in fatty acid and triglyceride metabolism [20]. …”
Section: Discussionmentioning
confidence: 99%
“…CYP7 α is the key rate-limiting enzyme for cholesterol transformation into bile acid in the liver, therefore promoting the excretion of cholesterol [19]. SREBP-2 is an important transcription factor, which could regulate fatty acid and cholesterol synthesis and impact the transcription of several genes involved in fatty acid and triglyceride metabolism [20]. …”
Section: Discussionmentioning
confidence: 99%
“…1), a major pharmacologically active component from roots of peonies, has been reported to possess anti-inflammatory7, antioxidant8, antihyperlipidemic activities9 and hepatoprotection10, with low toxicity and few side effects1112. Recent studies indicated that PF improved insulin resistance (IR) in NAFLD animal models by promoting fatty acid oxidation through the activation of peroxisome proliferator-activated receptor-alpha (PPARα)13 and by increasing the activity of AMP-activated protein kinase (AMPK)14. Our previous research demonstrated that PF had anti-inflammatory and hepatoprotective effects in NASH rats and that these effects due to inhibition of the Rho kinase/NF-κB signaling pathway in liver with NASH11.…”
mentioning
confidence: 99%
“…In present study, we identified paeoniflorin as the major component of BGH as revealed by the data using the UPLC. Some studies reported the paeoniflorin have hepato-protective and anti-atherosclerosis effect [35, 36]. Therefore, we suggest that BGH may be used as a functional food for prevention atherosclerosis and restenosis.…”
Section: Discussionmentioning
confidence: 79%